The Implementation of Active Learning Approach in Teaching Speaking at Universitas Muhammadiyah Parepare - Munir, Munir (La Parole : Journal of Language Teaching and Pedagogy, 2023)
This research aimed to find out the implementation an active learning of the teachers in teaching speaking at Universitas Muhammadiyah Parepare. The result would base on the teachers who taught the speaking lesson. Besides that, the response from the students also needed to compare with the teachers' answers. This research used the Qualitative Descriptive method. Where participants of this research are the English department speaking lecturers and some students who are taught by the lecturer concerned.Therefore, in collecting data for research researcher conducted interviews consisting of 20 open-ended questions to obtain the data from the teachers and the students. The researcher also collected data online using a questionnaire via Google Form The data will be analyzed and become the final results or findings of this study about the implementation of active learning. The result of this research showed the implementation of active learning able increase the students' vocabulary, then can improve their speaking skills of the students, makes students practice speaking more often than before, besides that active learning also can increase students' self-confidence, and last can increased students ' thinking and quality assurance in learning. Therefore the teachers or the participants of this research recommended active learning as a teaching approach.